PENGARUH PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP PERTUMBUHAN EKONOMI DAN IPM PADA DAERAH OTONOMI BARU DI PROVINSI KALIMANTAN BARAT - B2051141012, JULIANTO (Jurnal Ekonomi Daerah (JEDA), 2016)
Economic development is carried out in the new autonomous region aims to boost regional economic growth and well-being of people in the area. To support economic development activities have required a number of spending on education and health fields. This study aims to examine and analyze: 1. The effect of government expenditure in education (GSE) and government spending in health sector (GSH) towards economic growth (EG) and 2. The effect of government spending in education (GSE), government spending on health sector (GSH), and economic growth (EG) towards community welfare (CS) in the new autonomous region in West Kalimantan. The data used is the panel data time series of 7 new autonomous region during the period 2010 to 2014. The problems posed in this study is a one-way causal relationship between independent variables and the dependent variable. To determine the estimated value of the model equations used path analysis with data processing using software SPSS for windows 17.0 The results show a significant effect of GSE towards EG; GSH significant effect towards EG; GSE significant influence towards CS; GSH significant influence towards CS; and significant influence of EG towards CS Keywords : Government Spending In Education, Health, Economic Growth and Social Welfare